The Macroeconomic Determinants of Foreign Bank’s Profitability in Malaysia - Jiunn Yi, Pang; R, Devinaga; Yee Yen, Yuen; ., Suganthi; ., Shalini (International Journal of Engineering and Technology, 2018)
The topic of this research paper is “The macroeconomic determinants of foreign bank’s profitability in Malaysia. Panel data method were employed to analyze the cross sectional data and time series data collected  from 2006 to 2015 from a sample of ten foreign banks in Malaysia. Measurement of profitability is based on Return on assets which is a function of the macroeconomic determinants; GDP, inflation rate and real interest rate. The overall finding of this research study shows that GDP, inflation rate and real interest rate are the determinants of foreign banks in Malaysia. Those determinants were found to be statistically related on profitability and all of them had a positive relationship towards the profitability of foreign banks in Malaysia.